MICROBIOLOGICAL ANALYSIS OF PATHOGENS IN PATIENTS WITH SKIN CANCER (Web of Teachers: Inderscience Research, 2025)
In this study, microbiological investigations were conducted on 10 patients diagnosed with skin cancer. The obtained data indicate that microorganisms play a significant role in oncological processes of the skin. As a result, the presence of Staphylococcus aureus, Propionibacterium acnes, and Human Papillomavirus (HPV) infections was detected in tumor lesions.